Food or Non-Food? Family Hope Program (PKH) Impact Evaluation during Covid-19 Outbreak: Evidence from Bali - Prayasta, I Gede Heprin; Sri Budhi, Made Kembar; Sudibia, I Ketut; Yuliarmi, Ni Nyoman (Jurnal Ekonomi Kuantitatif Terapan; 2021: Vol. 14, No. 2, Agustus 2021 (pp.243-431), 2022)
The Family Hope Program (PKH) is a conditional cash transfer for alleviating poverty in Indonesia. The macro poverty is measured with basic needs approach through household consumption for food and non-food. The outbreak of the Covid-19 leads a deep contraction on the Bali’s economy which affect the level of household welfare. This study aimed to analyze the characteristics of PKH recipients, evaluate targeting accuracy and the impact of PKH on household consumption. The data analyzed were secondary data from SUSENAS March 2020 and primary data from in-depth interviews and FGD. The analytical methods in this study were Benefit and Incidence Analysis (BIA) and Propensity Score Matching (PSM). The results of the study found PKH mostly benefited by those among the lowest income group. PKH has a significant impact on the consumption of foodstuffs, but there is not strong enough to indicate an effect on non-food consumption during the pandemic outbreak.